Public policies to increase physical activity and reduce sedentary behavior: a narrative synthesis of "reviews of reviews" - Abdullah F. Alghannam; Jesse D. Malkin; Hazzaa M. Al-Hazzaa; Reem AlAhmed; Kelly R. Evenson; Severin Rakic; Reem Alsukait; Christopher H. Herbst; Saleh A. Alqahtani; Eric A. Finkelstein (Taylor & Francis Group, 2023)
Background Physical inactivity among the general population is of great concern in public health. Objective This narrative review aims to identify promising physical activity (PA) public policies based on the best available evidence from the literature. Methods The study is a narrative synthesis of 'reviews of reviews' of public policies designed to increase physical activity among either (a) youths or (b) the community at large. We searched the literature for reviews of reviews of public policies of any country relevant to physical activity, physical inactivity, or sedentary behaviour published since 1 January 2000, in four databases. Results Based on 12 reviews of reviews published between 2011 and 2022, we identified seven potentially effective PA public policies. Six of the seven were youth-based public policies that would be implemented in schools. The seventh was a policy aimed at establishing and promoting walking groups. Conclusions Policymakers seeking to increase PA should consider focusing on school-based PA policies and community-based walking groups, as this is where the evidence base is greatest. To implement these policies, pilot studies to assess the efficacy of such programmes in local communities should first be conducted due to methodological limitations in the underlying literature and questions of generalisability and reproducibility.